Building a 'Lofty, Beloved People's Amusement Centre': The socialist transformation of Shanghai's Great World (Dashijie) (1950–58). (13th May 2021) - XIAO, WENMING; LI, YAO
Abstract: Based on a detailed case study of the socialist transformation of the Shanghai Great World Amusement Centre (Dashijie), this article documents state-building efforts during the early years of the People's Republic of China (PRC). Between 1950 and 1958, the Communist regime incrementally transformed the power configuration within Dashijie, promoting dramatic changes in its personnel, institutional structures, drama performances, and physical space. Over the course of this process, Dashijie seemed to become a 'loftier' cultural organization in accordance with the aims of its transformation. This transfigured Dashijie, however, fell out of favour with the people of Shanghai. This multifaceted transformation process reflects considerable state capacities on the one hand and illustrates the complexity of state capacities—their unevenness and the limitations of a strong state—on the other. The complexity of state capacities thus shaped and was embedded in the process and outcome of this socialist cultural transformation. Since the Chinese state is once again making strenuous efforts at culture-building, an overview of cultural transformation in the early PRC era has important contemporary implications.